A Comprehensive Approach to Financial Risk Management: Analysis of Regulation, Innovation and Sustainability Through Semantic Literature Reviews - Mughni Lestari; Bagas Febriyanto; Novita Sari Marbun; Deni Sunaryo; Yoga Adiyanto (International Forum of Researchers and Lecturers, 2024)
Financial risk management is an important element in maintaining global economic stability. This study explores the relationship between regulation, technological innovation, and sustainability as three main pillars in modern financial risk management. Using the Semantic approach Literature Review (SLR), this study analyzes the literature from 50 selected scientific articles published between 2018 and 2024. The results of the study show that regulations such as Solvency II and IFRS 17 strengthen transparency and accountability, while innovative technologies such as parametric insurance and resilience bonds increase the efficiency of risk management. In addition, sustainability, which is realized through initiatives such as green insurance and sharia insurance, is a key pillar in mitigating systemic risk.However, the study identified a number of challenges, including fragmentation of regulations across countries, limited access to technology in developing countries, and moral hazard in implementing sustainability. To overcome these obstacles, a collaborative strategy involving governments, the private sector, and the international community is needed to harmonize global regulations, strengthen technology infrastructure, and improve technology and sustainability literacy. This study contributes to presenting a comprehensive financial risk management framework by recommending strengthening the synergy between regulation, technology, and sustainability. This study also provides practical guidance to address global challenges in financial risk management, while also providing a basis for further in-depth research on specific sectors, geographic regions, and the integration of technology and sustainability.